2003
DOI: 10.1128/aem.69.3.1435-1441.2003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Genetic Diversity among Pseudomonas citronellolis Strains Isolated from Oily Sludge-Contaminated Sites

Abstract: The diversity among a set of bacterial strains that have the capacity to degrade total petroleum hydrocarbons (TPH) in soil contaminated with oily sludge (hazardous hydrocarbon waste from oil refineries) was determined. TPH is composed of alkane, aromatics, nitrogen-, sulfur-, and oxygen-containing compound, and asphaltene fractions of crude oil. The 150 bacterial isolates which could degrade TPH were isolated from soil samples obtained from diverse geoclimatic regions of India. All the isolates were biochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
66
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(73 citation statements)
references
References 31 publications
(15 reference statements)
4
66
0
3
Order By: Relevance
“…This could be because of unmeasured environmental variables. For instance, it has been reported that the types of oil contaminants and age of site contamination could influence the microbial genetic diversity (Bhattacharya et al, 2003). The composition and structure of hydrocarbons in oil contaminants are highly variable in different oil-contaminated fields, which could affect the microbial functional gene composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be because of unmeasured environmental variables. For instance, it has been reported that the types of oil contaminants and age of site contamination could influence the microbial genetic diversity (Bhattacharya et al, 2003). The composition and structure of hydrocarbons in oil contaminants are highly variable in different oil-contaminated fields, which could affect the microbial functional gene composition.…”
Section: Discussionmentioning
confidence: 99%
“…Certain hydrocarbon-degrading taxa become dominant in oil-impacted environments because of natural selection resulting from the pressure of oil contaminants (Margesin et al, 2003;Head et al, 2006). Other environmental variables also influence microbial distribution, such as regional climate (Bhattacharya et al, 2003;Maila et al, 2006), soil type and characteristics (Hamamura et al, 2006) and vegetation (Joner et al, 2001). To date, most of the efforts to describe microbial communities in oil-contaminated fields have been focused on phylogenetic composition.…”
Section: Introductionmentioning
confidence: 99%
“…However, the approach to remediate dumps through vegetation development and reduce risks associated with the ash dumps has received little attention (Haynes, 2009;Rau et al, 2009). Most of the restoration programs at the fly ash dumps face bottlenecks of poor knowledge of the relationship between plant-soil feedback and its impact on soil microbial functional diversity (Mohmmed et al, 2001;Bhattacharya et al, 2003;Rau et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…(Liu et al 2001), Pseudomonas citronellonis (Bhattacharya et al 2003), Pseudomonas oleovorans (Witholt et al 1990), Pseudomonas aeruginosa (Belhaj et al 2002), Hormoconis resinae (Solana & Gaylarde 1995), Aspergillus niger (Volke-Sepulveda et al 2003) and three bacterial enriched consortia isolated from polluted areas as described by Okeke & Frankeberger (2003).…”
Section: Introductionmentioning
confidence: 99%